A Simple and Highly Stable Porous Gold‐based Electrochemical Sensor for Bisphenol A Detection. Issue 2 (25th August 2016) - Wannapob, Rodtichoti; Thavarungkul, Panote; Dawan, Supaporn; Numnuam, Apon; Limbut, Warakorn; Kanatharana, Proespichaya
Abstract: A porous gold electrode with a uniform pore size was prepared by a simple single potential step method. It provided around 19 times more surface area than a bare gold electrode. The porous gold electrode, without any modification, exhibited good electrocatalytic activity towards the oxidation of bisphenol A (BPA). The effect of the pH and scan rate, on the porous gold electrode was studied and discussed. Under optimum conditions of the flow system, the calibration plot of BPA was linear over a wide range of concentration, from 2.0 nM to 800 nM (R 2 =0.999), and the detection limit was 2.0 nM (s/n=3). It was of interest that, the porous gold electrode showed an exceptional result in minimizing the fouling from the oxidation product of BPA and led to a very high operational stability of the electrode for the detection of BPA (560 consecutive times). The porous gold electrode showed good fabrication reproducibility and can be used to detect bisphenol A that leached from baby bottles and drinking water bottles. The obtained results were in good agreement with the GC‐MS method ( P >0.05). Abstract :